2013
DOI: 10.1111/jpc.12127
|View full text |Cite
|
Sign up to set email alerts
|

Parental stress in a paediatric intensive care unit in Punjab, India

Abstract: It is concluded that there is significant stress among parents of children admitted to an Indian PICU, and stress factors are different from studies done in developed countries. Mothers and young parents were more stressed. Type of family, income, education, number and age of children did not affect level of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
1
24
2
Order By: Relevance
“…There are only a few studies of this kind done in India. 7,8 Hence this study was taken to determine the clinical and sociodemographic factors leading to stress among parents whose children were admitted in PICU of a tertiary care hospital in Mangalore.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies of this kind done in India. 7,8 Hence this study was taken to determine the clinical and sociodemographic factors leading to stress among parents whose children were admitted in PICU of a tertiary care hospital in Mangalore.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in India have found that families with low socioeconomic status and low literacy rates have less awareness about their child's disability (Verma & Kishore, 2009;Prakash, 2010;Pooni et al, 2013). This study suggests that lack of knowledge about their child's disability is commonly identified among all families, regardless of their socioeconomic status and literacy level.…”
Section: Discussionmentioning
confidence: 75%
“…Recent evidence suggests that due to the burden of care, parents of children with disabilities are stressed and frustrated (Cherry, 1989;Verma & Kishore, 2009;Pooni et al, 2013). Cultural beliefs about disability and socioeconomic status also affect parental perceptions (Cherry, 1989;Pooni et al, 2013). Educating parents about their child's disability is now becoming an integral part of the treatment plan for the paediatric physiotherapist (Crais et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations